Frailty as a sequela of burn injury: a post hoc analysis of the "RE-ENERGIZE" multicenter randomized-controlled trial and the National Health Interview Survey - Panayi, Adriana C.; Heyland, Daren K.; Stoppe, Christian; Jeschke, Marc G.; Knoedler, Samuel; Tapking, Christian; Didzun, Oliver; Haug, Valentin; Bigdeli, Amir Khosrow; Kneser, Ulrich; Orgill, Dennis P.; Hundeshagen, Gabriel (Military medical research, 2024)
With advancements in burn treatment and intensive care leading to decreased mortality rates, a growing cohort of burn survivors is emerging. These individuals may be susceptible to frailty, characterized by reduced physiological reserve and increased vulnerability to stressors commonly associated with aging, which significantly complicates their recovery process. To date, no study has investigated burns as a potential risk factor for frailty. This study aimed to determine the short-term prevalence of frailty among burn survivors’ months after injury and compare it with that of the general population.